2007
DOI: 10.1016/j.crte.2007.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Air quality in Europe during the summer of 2003 as a prototype of air quality in a warmer climate

Abstract: The extremely warm summer of 2003, with its August heat wave, is taken as a prototype of future summer weather in Europe. The stagnant circulation led to accumulation of heat and pollutants, increased forest fires, and induced high ozone and particulate matter levels. After a description of the meteorological conditions encountered, we review here the effects of the heat-wave meteorology on photochemistry, wild fires, and particulate matter, at the continental and urban scales. We discuss the extent to which t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
36
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
3
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(36 citation statements)
references
References 58 publications
0
36
0
Order By: Relevance
“…If conditions like 1988 become more frequent as a result of global warming, the implications for air quality could be severe. Similar inferences can be made for Europe, where the summer 2003 heat wave was associated with exceptionally high ozone (Vautard et al, 2005(Vautard et al, , 2007Guerova and Jones, 2007;Solberg et al, 2008).…”
Section: Introductionmentioning
confidence: 51%
See 1 more Smart Citation
“…If conditions like 1988 become more frequent as a result of global warming, the implications for air quality could be severe. Similar inferences can be made for Europe, where the summer 2003 heat wave was associated with exceptionally high ozone (Vautard et al, 2005(Vautard et al, , 2007Guerova and Jones, 2007;Solberg et al, 2008).…”
Section: Introductionmentioning
confidence: 51%
“…Increasing frequency of wildfires from droughts in the future climate could be yet another important factor driving PM increases. The anomalously hot summer 2003 in Europe was associated with record wildfires that significantly degraded air quality for both PM and ozone (Vautard et al, 2007;Solberg et al, 2008). The GCM-CTM study of Spracklen et al (submitted for publication) including projection of climate-driven increase in wildfires finds a 0.5 mg m À3 increase in carbonaceous PM in the western U.S. in summer.…”
Section: Particulate Mattermentioning
confidence: 99%
“…According to Vautard et al [7], the summer of 2003 provides a powerful case study for anticipating the impacts of summertime climate change in Europe.…”
Section: Study Periodmentioning
confidence: 99%
“…Research conducted across many settings, including both observational and model perturbation studies, suggests that elevated O 3 concentrations are most strongly linked with increases in temperature (Jacob and Winner, 2009;Pearce et al, 2011). Exceptionally high O 3 levels were observed in Europe in August 2003 associated with hot and dry heat-wave conditions (Vautard et al, 2007). In an analysis of covariance performed on observed daily O 3 maxima in Switzerland during the 1992-2002 period, Ordónez et al (2005) found that temperature and global radiation accounted for most of the meteorological variability in summer O 3 concentration.…”
mentioning
confidence: 99%